Thematic Analysis of Extremism in Contemporary Social Behavior Through Interpretations of Islamic Teachings (Al-Aasar, 2025)
Islam is a religion of love and non-violence. Islam emphasizes the rights of people. With the passage of time, living conditions have gotten better., the literacy rate here is much better than the previous eras. Development can be observed in every sector. And there has also been progress in the field of education. The living standard of the people has better to a great extent. Despite all this, when we look at human values and social practices, there is a lot of disappointment. In view of this situation, several aspects can be taken into consideration in this research, we have discussed some important social attitudes of the people. purposive sampling technique was use in this research and 40 participants were selected from four different categories. Self-developed interviews consisted of 20 items based on four categories. The researcher was personally visited and collect the data from the survey participants. The results of the study highlighted people have unequal treatment with the minorities, women, orphans and subordinates. Despite the remarkable increase in the literacy rate, our attitudes like extremism, jealousy, selfishness can be clearly observed. Suggestions were provided based on the findings.